Personal factors of resilience and self-concept in primary school students of Metropolitan Lima - Matalinares Calvet, María (2011)
The research presented was to establish whether there was any connection between the personal factors of resilience and self-concept in primary school students in Lima. For its performance was evaluated at 420 students, of both sexes, aged between 10 and 12 years, who were in the fifth and sixth grades of primary schools from different Lima state who completed the inventory of factors personal resilience proposed by Salgado (2005) and Self-Concept Questionnaire proposed by Belen García Garley, adapted to our reality for purposes of the investigation. Results showed that correlation exists between the personal factors of resilience and self-concept. He also found a relationship between the factors self-esteem and empathy with all components of the self-concept. When comparing men with women’s self-concept were no significant differences in the physical, social and family in favor of women. Finally, when comparing men and women in the resilience factors found significant differences in favor of women in self-esteem, empathy and resilience.